UNCOVERING ARABIC LANGUAGE ERRORS IN CONVERSATIONAL CONTEXT: AN ANALYSIS OF DERIVATION AND INFLECTION ASPECTS - Sovinaz; Achmad Tito Rusady (ALSINATUNA, 2023)
This study aims to analyze Arabic errors in daily conversation activities from the aspect of inflection and derivation in morphological studies, as well as explain the types and forms of language errors, classify them, analyze their forms and correct them, and finally analyze the factors that cause language errors. It happened. The object of this research is a 5th grade female student at the Daarul Ukhuwwah Putri 2 Islamic boarding school in Malang, East Java. This study uses a qualitative method with a descriptive approach. Data collection techniques in this study were observation, interviews, and oral tests. Data analysis was carried out by following procedures or steps in analyzing language errors, namely collecting data, identifying and classifying errors, sorting errors, identifying error areas, and correcting errors. The results of this study explain that language errors that are often made by 5th grade students when speaking are incorrectly placing the forms of Ḍamir muttaṣil, fi'il maḍi, isim fā'il, and masdar, as well as errors that occur by accident. The mismatch in word forms in the pronunciation sentence لِتَسْتَعِدْ لِلدِّرَاسَةِ, which should use the masdar form, then becomes اِستِعْدَادًا للدِّرَاسَةِ and in simplifying the sentence مَاعِنْدِي الفلُوس, becomes مُفْلِسٌ, which is the fa'il ism of the word أَفْلَسَ. There are two distinct categories responsible for the occurrence of language errors: internal factors and external factors. Internal factors occur from the speaker's self, and external factors occur due to environmental influences experienced by the speaker. Although these two factors are complex and multidimensional, the teacher's efforts in language justification can still be made and these errors can still be corrected.